PENINGKATAN PENGETAHUAN TENTANG INFEKSI MENULAR SEKSUAL MELALUI PROGRAM EDUKASI 'REMAJA TAAT’ - Chellyadiza, Alfitri; Azwari, Ayu Riana Sari; Rahman, Fauzie; Alisa, Fitralina Nur; Fitriani; Afifah, Halisyah Nur; Noorsyifa; Zahra, Novyananda Aulya (Universitas Mataram, 2024)
Sexually Transmitted Infections (STIs) are a significant global health problem, especially among adolescents who are in an important developmental phase. This research aims to increase students' knowledge and awareness about STIs through counseling at MAN 4 Banjar. Based on initial data, many students still lack knowledge about STIs. Counseling activities were carried out by lectures, discussions, mini games, and questions and answers, followed by pre-test and post-test to measure changes in knowledge. The results of the study showed a significant increase in students' knowledge about Sexually Transmitted Infections (STIs) after participating in counseling. Knowledge related to causes, modes of transmission, and disease while STI prevention attitudes increased from 48.27% to 68.96%. The Wilcoxon Signed Rank test confirmed a significant increase in post-test scores (p < 0.05) compared to the pre-test, with the average score increasing from 90.34 to 97.24. These findings confirm the effectiveness of counseling in improving students' understanding of STIs. Counseling at MAN 4 Banjar is effective in increasing students' knowledge about STI prevention, emphasizing the importance of comprehensive sexual education and the role of schools in creating an environment that supports adolescent sexual health.